A infiltração de agentes de polícia na investigação criminal de organizações criminosas e o equilíbrio de proteção aos direitos fundamentais - Miranda, Murilo Franco de (2020)
This paper aims to analyze the undercover agents in the investigation of criminal organizations with a focus on the balance of protection of fundamental rights. The growth of criminal organizations threatens the Democratic Rule of Law and its institutions insofar as it affects legal assets of constitutional dignity and interferes with the provision of essential public services. It addresses, in a historical context, the emergence of organized crime, its characteristics, the repression of crimes with the help of people and the legislative process that gave rise to the Criminal Organizations Law. In this perspective, the undercover agent, as a special means of obtaining evidence, is analyzed in the national legal system as well as its use in the repression of criminal organizations. The procedural aspects related to the execution of the measure are presented and controversial issues such as, for example, the legitimacy to execute it and the criminal liability of the infiltrated agent are reasoned. The case law of the European Court of Human Rights and the Federal Supreme Court related to the use of the measure is discussed, as well as its transversality with the activity of State intelligence and public security. The balance of protection and the compatibility of the measure with fundamental rights occurs by linking the Executive, Legislative and Judiciary Powers and the Public Ministry to the principle of proportionality, sometimes prohibiting excesses and sometimes prohibiting the deficient protection of legal, social, collective and diffuse.